2020
DOI: 10.1002/ps.5782
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation of nicotinic acetylcholine receptor (nAChR) α6 as a target of spinosyns in Spodoptera exigua utilizing the CRISPR/Cas9 system

Abstract: BACKGROUND: The beet armyworm, Spodoptera exigua, is a serious agricultural pest that is primarily controlled using chemical insecticides. Recently, resistance to the insecticide spinosad has been described in S. exigua field populations. To date, there has been no functional evidence proving the involvement of the nicotinic acetylcholine receptor (nAChR) ⊍6 mutation in spinosad resistance in S. exigua.RESULTS: In this study, using the CRISPR/Cas9 genome-editing system, a homozygous strain (Se⊍6-KO) with appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…In the present work, the obtained Cry1Fa resistance was confirmed to be genetically associated with the 8-bp deletion of OfABCC2, which excludes the CRISPR-mediated off-target effects on resistance phenotype. We analyzed 18 research cases that employed the CRISPR/Cas9 system to manipulate the resistance genes to Bt toxins or insecticides, and found that only five of them performed linkage analysis between acquired resistance and the introduced mutation, including the knockout of the cadherin gene in H. armigera [40], nicotinic acetylcholine receptor α6 subunit in P. xylostella and S. exigua [41,42], the ryanodine receptor G4946E mutation in Drosophila melanogaster [43], and a CYP9M10 gene in Culex quinquefasciatus [44]. We therefore recommend that when CRISPR-based gene editing is conducted to verify the function of a candidate gene, it is necessary to perform a genetic linkage analysis in order to clarify whether there are off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the obtained Cry1Fa resistance was confirmed to be genetically associated with the 8-bp deletion of OfABCC2, which excludes the CRISPR-mediated off-target effects on resistance phenotype. We analyzed 18 research cases that employed the CRISPR/Cas9 system to manipulate the resistance genes to Bt toxins or insecticides, and found that only five of them performed linkage analysis between acquired resistance and the introduced mutation, including the knockout of the cadherin gene in H. armigera [40], nicotinic acetylcholine receptor α6 subunit in P. xylostella and S. exigua [41,42], the ryanodine receptor G4946E mutation in Drosophila melanogaster [43], and a CYP9M10 gene in Culex quinquefasciatus [44]. We therefore recommend that when CRISPR-based gene editing is conducted to verify the function of a candidate gene, it is necessary to perform a genetic linkage analysis in order to clarify whether there are off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a 2‐nt deletion introduced by CRISPR/Cas9 resulted in a truncated receptor that conferred resistance to spinosyns in P. xylostella 39 . A high level of resistance to spinosyns has also been found in a CRISPR/Cas9‐based Seα6‐KO strain of S. exigua with a 1760‐bp deletion located between TM3‐TM4 in Seα6 , 42 while nonfunctional Haα6 produced by a 5‐bp insertion induced a pre‐mature stop codon via CRISPR/Cas9 genome editing that was associated with reducing susceptibility to spinosyns in H. armigera 65 . To understand the causality between Aaeα6 mutations and spinosad resistance in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Ribonucleoprotein complexes, including Cas9 nuclease and single‐guide RNA (sgRNA), induce a double‐stranded DNA break at a protospacer adjacent motif (PAM) in a given genetic sequence, which can then be repaired using either nonhomologous end joining or homology‐directed repair 34–36 . CRISPR/Cas9 has been widely utilized in many different species to elucidate the genetic mechanism of insecticide resistance, including knock‐out or knock‐in mutations in target genes such as nAChR α6, P‐glycoprotein, ABC transporters, ryanodine receptors, cadherin and the GABA‐gated chloride channel, and can alter an insect's susceptibility to different insecticides 32,33,37–43 . In Aedes aegypti , which is a potent vector of several arboviruses, target‐directed mutagenesis using the CRISPR/Cas9 system 35,36,44 could provide useful information on the potential causal relationship between mutations in the target receptor and insecticide resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CRISPR/Cas9 tool has been employed for knockout of many insect genes including H. armigera, S. exigua etc. Knockout mutations in a-6nicotinic acetylcholine receptor (nAchR) through CRISPR/Cas9 showed resistance to an insecticide, spinosyn, both in H. armigera and S. exuigua (Zuo et al 2020;Wang et al 2020a, b). Knockout of two ABC transporters, PxABCC2 and PxABCC3 in lepidopteran pest Plutella xylostella through CRISPR/Cas9 tool, resulted higher level of resistance to cry1Ac protoxin compared to susceptible strains (Guo et al 2019).…”
Section: Crispr-cas-mediated Genome Editing For Insect Controlmentioning
confidence: 99%